Rogue waves as modulational instability result in one-dimensional nonlinear triatomic acoustic metamaterials - Justin, Mibaile; Joseph, Mora; David, Vroumsia; Azakine, Sylvere; Betchewe, Gambo; İnç, Mustafa; Serge, Doka Yamigno (Elsevier, 2023)
In this study, a triatomic acoustic nonlinear metamaterial was modelled. It is a network of identical periodic unit cells made up of three different masses. These masses interact with connections modelled by springs whose stiffnesses are linear and nonlinear. Handling the motion equations of nth unit cell, the semidiscrete approximation method is used to extract the three-component coupled nonlinear Schrodinger equations. The dispersion relationship was determined. The results showed that the dispersion relation of the one-dimensional triatomic chain contained an acoustic branch and two optical branches. The dispersion curves show that the proposed acoustic metamaterial exhibits two local resonance bandgaps independent of spatial periodicity. The spectral range and frequency bandgap are related to the mass of the three atoms in the original cell. Based on the theory of linear stability analysis, modulation instability is the condition for the existence of rogue waves. Analytically, it is shown that modulational instability and rogue wave phenomena are strongly influenced by variations in the nonlinearity, dispersion, and diffraction terms, which contain the values of the masses and stiffnesses.
Keywords: Triatomic nonlinear acoustic metamaterial; Three-component nonlinear Schrodinger; equations; Modulational instability; Rational rogue waves